Examining the Differences of Gender on Psychological Well-being - Salleh, Nurul ‘Aaina Binti; Mustaffa, Che Su (International Review of Management and Marketing, 2016)
The purpose of this paper is to determine whether male and female differ with regard to aspects of psychological well-being among flood victims. This study is based on a quantitative approach using cross-sectional survey. The research sample consisted of 300 flood victims who were moved to shelters in the state of Kelantan. Research tools was Ryff's Psychological Well-being Scale developed by Carol Ryff (1989). The results showed that there was no significant difference between male and female in psychological well-being (t=1.194, p>0.05). Besides that, no gender differences were found in term of all the dimensions in psychological well-being (autonomy, environmental mastery, positive relations with others, self-acceptance, and personal growth) among flood victims. It implies that there was no dissimilarity in term of perception toward psychological well-being for those male and female respondents. Keywords: Psychological Well-being, Gender, Flood Victim JEL Classifications: I18, H84, Q54